Adherence to Antihypertensive Medications among Nepalese Hypertensive Patients at A Tertiary Care Hospital of Nepal - Palikhey, Anjan; Jaisi, Sandeep; Sharma Banjade, Dilip; Thapaliya, Ishwor; Shrestha, Laxmi; Kumar Shrivastava, Amit; Kandel, Kamal (Journal of National Heart and Lung Society Nepal, 2024)
Background: Hypertension remains a significant public health concern globally, contributing to the burden of cardiovascular disease and associated morbidity and mortality. Effective management of hypertension often relies on adherence to antihypertensive medication regimens. However, non-adherence to prescribed medications presents a formidable challenge in achieving optimal blood pressure control and preventing complications. The main objective of this study was to find out the adherence to antihypertensive medication among Nepalese hypertensive patients at a tertiary care hospital. Methods: This analytical cross-sectional study was conducted at the outpatient department of medicine of UCMS-TH. A total of 384 participants were involved in the study, where the adherence rate to anti-hypertensive medication was collected using Morisky Medication Adherence Scale (MMAS-8). SPSS version 22 was used to record and analyze the data, and the descriptive results were presented as numbers and percentages. Chi-square test was used to determine the association between adherence and other variables at 95% confidence interval. Results: The study found a very high percentage (85.70%) of adherence to antihypertensive drugs. Forgetfulness was the major reason for the non-adherence 30(54.50%). Age group and educational status of the participants were significantly associated with adherence rate (p